2001
DOI: 10.1021/jf001443p
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Assisted Extraction of Antioxidative Phenols from Black Currant Juice Press Residues (Ribes nigrum)

Abstract: Enzymatic release of phenolic compounds from pomace remaining from black currant (Ribes nigrum) juice production was examined. Treatment with each of the commercial pectinolytic enzyme preparations Grindamyl pectinase, Macer8 FJ, Macer8 R, and Pectinex BE, as well as treatment with Novozym 89 protease, significantly increased plant cell wall breakdown of the pomace. Each of the tested enzyme preparations except Grindamyl pectinase also significantly enhanced the amount of phenols extracted from the pomace. Mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
128
0
11

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(149 citation statements)
references
References 27 publications
10
128
0
11
Order By: Relevance
“…EAE of phenolic antioxidants from grape pomace during wine production was tested by Meyer et al (1998) who found a correlation between yield of total phenols and degree of plant cell wall breakdown by enzyme. Landbo and Meyer (2001) showed improved release of phenolic compounds from Ribes nigrum pomace using various enzymes. Li et al (2006) extracted total phenolic contents from five citrus peels (Yen Ben lemon, Meyer lemon, grapefruit, mandarin and orange) by EAAE using different enzymes and the recovery was highest with celluzyme MX.…”
Section: Enzyme-assisted Extraction (Eae)mentioning
confidence: 99%
“…EAE of phenolic antioxidants from grape pomace during wine production was tested by Meyer et al (1998) who found a correlation between yield of total phenols and degree of plant cell wall breakdown by enzyme. Landbo and Meyer (2001) showed improved release of phenolic compounds from Ribes nigrum pomace using various enzymes. Li et al (2006) extracted total phenolic contents from five citrus peels (Yen Ben lemon, Meyer lemon, grapefruit, mandarin and orange) by EAAE using different enzymes and the recovery was highest with celluzyme MX.…”
Section: Enzyme-assisted Extraction (Eae)mentioning
confidence: 99%
“…The processing of the fruits results in larger and higher amount of co-products and wastes which can be utilised. In fruit juice production from berries, press residues (cakes) are formed in large quantities, which contain several valuable nutrients, ingredients and compounds (Landbo and Meyer 2001;Hilz et al 2005). These residues are suitable for pectin recovery, though their pectin content is somewhat lower than other typically pectinrich fruits.…”
Section: Introductionmentioning
confidence: 99%
“…The result indicates that a high solid-to-solvent ratio acts as a driving force to increase the concentration gradient, resulting in an increase of diffusion of extractives into the solvent giving a greater extraction. Previous studies also reported larger concentration gradient to be favourable for mass transfer across solid-liquid interface for better antioxidant extraction (Landbo and Meyer, 2001;Al-Farsi and Lee, 2008). ISSN: 2348ISSN: -1900 Horizon e-Publishing Group However the phenomenon of the static trend in phenolic antioxidant extraction after the ratio of 1:20 can be explained by Fick's Second Law of Diffusion where it is stated that no rise in extraction is possible after an equilibrium is achieved (Zhang et al, 2007), indicating the solid to solvent ratio of 1:20 as the equilibrium point and hence the optimised condition for total phenol and antioxidant extraction from the sample.…”
Section: Effect Of Solid To Solvent Ratiomentioning
confidence: 95%